The Legal Problems of Inheritance Share in the Charter Capital of LLC for Surviving Spouses - Yu. N. Strazhevich; O. I. Bosyk (Сибирское юридическое обозрение)
The legal problems of an inheritance share in charter capital of LLC by the surviving spouse are under consideration. The article focuses on normative legal regulation and law enforcement practice in this sphere. The authors offer an algorithm of the registration of rights to inheritance share in LLC.